2018
DOI: 10.1186/s41016-018-0134-7
|View full text |Cite
|
Sign up to set email alerts
|

Pipeline for previously stented basilar trunk aneurysm: a case focusing on how the pipeline should be deployed

Abstract: Background: Recurrent, previously stented basilar trunk aneurysms pose significant challenges to either microsurgical clipping or traditional endovascular treatment. We here presented an intriguing case that was successfully treated by the pipeline embolization device (PED; ev3/Covidien Neurovascular, Irvine, California, USA). Case presentation: A 62-year-old male found a recurrent aneurysm, which had been treated with coiling and stentassisted coiling before. The patient came to our center seeking for a third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Since craniotomy clipping is very difficult, EVT remains the first procedure of choice for BA trunk aneurysms ( 14 ). In the current choices for EVT, the flow-diverting stent has been widely used in cerebral aneurysms ( 2 , 15 ). However, the flow-diverting stent is rarely used for BA trunk aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Since craniotomy clipping is very difficult, EVT remains the first procedure of choice for BA trunk aneurysms ( 14 ). In the current choices for EVT, the flow-diverting stent has been widely used in cerebral aneurysms ( 2 , 15 ). However, the flow-diverting stent is rarely used for BA trunk aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported procedural events related to implanting PED in a previous stent, with no corresponding scheme provided to avoid these technical difficulties (6, 13). The strategy to deploy the PED remains controversial (5,13,14). There are four types of overlap between a newly implanted PED and a previously deployed stent: (1) PED only covers the proximal end of the previous stent, (2) PED only covers the distal end of the previous stent, (3) PED covers both the proximal and distal ends of the previous stent, and (4) PED is deployed within the previous stent.…”
Section: Discussionmentioning
confidence: 99%
“…Chalouhi et al ( 5) deployed the PED within the indwelling stent or ensured sufficient PED length to anchor on the normal artery distally and proximally to the stent in situ. On the contrary, Liang et al (13) deemed to deploy the PED within the indwelling stent, that is to say, placing the proximal and distal ends of the FD device within the previous stent so that the PED would not be stuck at the struts of the previous stent. This resembled the FRED flow diverter, which has the additional benefit of lowering postprocedural ischemia (15).…”
Section: Discussionmentioning
confidence: 99%